If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-8x=5x-10x-12.
We move all terms to the left:
6-8x-(5x-10x-12.)=0
We add all the numbers together, and all the variables
-8x-(-5x-12)+6=0
We get rid of parentheses
-8x+5x+12+6=0
We add all the numbers together, and all the variables
-3x+18=0
We move all terms containing x to the left, all other terms to the right
-3x=-18
x=-18/-3
x=+6
| 2/3(6x+18=3x-15 | | 11x+4+5x+8=60 | | (3a+2a)+10=20 | | |y-7|=6 | | (6+n)(2)=10+n | | c–4=–3 | | -20=-4=-6x | | 3a+2a)+10=20 | | 50/100=x/80 | | -3+2x=10=x | | 14x-8=10x-16 | | 5(a-4)=18 | | 90+x+47+x+67=180 | | 21x-297+13x=79 | | 5^3x-5=47 | | -y+12=5 | | 11-(5-6x)=0 | | 8n=36+(-n) | | -57x+57=-75+75 | | 43.8/100=x/75 | | 2(13-7x)=x-19 | | n/–7+70=66 | | -13x11=x(x) | | 19+6m=25 | | n–7+70=66 | | 2x-1=x+(-6) | | -13x11=6(x) | | -20-10e=-70 | | 30t+25=-20t+100 | | 15+2.50r=30 | | 10x2+8x=1 | | x-16=42/6 |